Efficient Quantum Algorithms for GHZ and W States, and Implementation on the IBM Quantum Computer. Issue 5 (23rd April 2019) - Cruz, Diogo; Fournier, Romain; Gremion, Fabien; Jeannerot, Alix; Komagata, Kenichi; Tosic, Tara; Thiesbrummel, Jarla; Chan, Chun Lam; Macris, Nicolas; Dupertuis, Marc‐André; Javerzac‐Galy, Clément
Abstract: Efficient deterministic algorithms are proposed with logarithmic step complexities for the generation of entangled GHZ N and W N states useful for quantum networks, and an implementation on the IBM quantum computer up to N = 16 is demonstrated. Improved quality is then investigated using full quantum tomography for low‐ N GHZ and W states. This is completed by parity oscillations and histogram distance for large‐ N GHZ and W states, respectively. Robust states are built with about twice the number of quantum bits which were previously achieved. Abstract : Entangled GHZ N and W N quantum states can be efficiently and deterministically generated on the IBM quantum computer with 16 qbits up to N = 16 . The proposed scheme features logarithmic step complexities. Resulting improved quality is then characterized using full quantum tomography for low‐ N, while parity oscillations and histogram distance are used for large N values.